AMIL: Localizing Neighboring Mobile Devices Through a Simple Gesture - Han, Hao; Yi, Shanhe; Li, Qun; Shen, Guobin; Liu, Yunxin; Novak, Ed (INFOCOM 2016, 2016)
Smartphone users are often grouped to exchange files or perform collaborative tasks when meeting together.We argue that the location information of group members is critical to many mobile applications. Existing localization solutions mostly rely on anchor nodes or infrastructures to perform ranging and positioning. These approaches are inefficient for ad hoc scenarios. In this paper, we propose AMIL, an Acoustic Mobility- Induced TDoA (Time-Difference-of-Arrival)-based Localization scheme for smartphones. In AMIL, a smartphone user can use simple gestures (e.g., hold the phone and draw a triangle in the air) to quickly obtain the relative coordinates of neighboring mobile devices. We have implemented and evaluated AMIL on off-the-shelf smartphones. The field tests have shown that our scheme can achieve less than three degree orientation errors and can successfully build a simple map of 12 people in an office room with average error of 50cm.